2014
DOI: 10.7150/ijms.7142
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Metastasis-associated in Colon Cancer-1 Gene Predict the Recurrence of Hepatocellular Carcinoma after Transplantation

Abstract: Background: The newly identified metastasis-associated in colon cancer-1 (MACC1) gene is involved in angiogenesis, epithelial-to-mesenchymal transition (EMT), invasiveness, and metastasis in a variety of malignancies. Overexpression of MACC1 gene is a prognostic marker for poor outcome of hepatocellular carcinoma (HCC) patients. However, the association between genetic polymorphisms of MACC1 gene and poor outcome in HCC has been not been performed. We therefore investigated the correlation of MACC1 single nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Meanwhile, both rs1990172 (A29858C) and rs3095009 (C77360T) are not in coding exon but in intron regions, which exhibit no impact on coding exon of MACC1 gene [13,18]. Moreover, Zheng et al found no significant difference in the allele or genotype distribution of the MACC1 SNPs between hepatocellular carcinoma (HCC) tissues and adjacent normal tissues, which showed that MACC1 SNPs probably have no influence on the risk of development of HCC [35].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, both rs1990172 (A29858C) and rs3095009 (C77360T) are not in coding exon but in intron regions, which exhibit no impact on coding exon of MACC1 gene [13,18]. Moreover, Zheng et al found no significant difference in the allele or genotype distribution of the MACC1 SNPs between hepatocellular carcinoma (HCC) tissues and adjacent normal tissues, which showed that MACC1 SNPs probably have no influence on the risk of development of HCC [35].…”
Section: Discussionmentioning
confidence: 99%
“…It is also involved in angiogenesis and lymphangiogenesis to promote tumor invasion and metastasis [43, 44]. In turn, these microvessels and microlymphantic vessels sustain CSCs that further promote tumor invasion and metastasis, thus creating a positive cycle of tumor advancement.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, MACC1 could be bound to the promoter of the MET gene and activate the HGF/MET signaling pathway to promote cancer cell proliferation, invasion, and metastasis [3, 4]. Furthermore, it could promote angiogenesis and lymphangiogenesis to lead to cancer cell invasion and metastasis [40, 41]. Moreover, KAI1 is able to be bind to c-MET to form a complex or quench the activation of HGF, thus preventing the activation of MACC1 to inhibit the migration of tumor cells [42, 43].…”
Section: Discussionmentioning
confidence: 99%